Analisis Data Sentinel-2 Untuk Mendukung Pariwisata Kawasan Wakatobi - Artaningh, Febzi; Anggraini, Tania Septi; Sihotang, Elstri; Sakti, Anjar Dimara; Agustan, Agustan (Masyarakat Ahli Penginderaan Jauh Indonesia (MAPIN) /Indonesian Society of Remote Sensing (ISRS), 2020)
Sentinel-2 Data Analysis to Support Special Interest Tourism in the Wakatobi Region Abstract. Tourism has a role for power improvement of the regional economy; therefore, it is important to do a good plan, management, and monitoring the tourism areas for sustainable goals. Satellite-based remote sensing methods are proven reliable in getting area information effectively and regularly. The Sentinel-2 satellites monitoring land cover changes regularly thus that it can be used to analyze the environmental carrying capacity for tourism. Sentinel-2 data that consists of several scenes at two-time observations were processed by mosaicking and spectral color composite strategies. The Wakatobi coastal uniqueness was analyzed by the vegetation index method combined with tidal data. There are several regions that were indicated to have spectral changes over five months, with an area approximately 30,55 km2. These interesting objects have the potential to support tourism in the Wakatobi region.